Long term outcomes of patients transplanted for hepatocellular carcinoma with human immunodeficiency virus infection. Issue 8 (August 2019) - Eman, Pedro; Chacon, Eduardo; Gupta, Meera; Berger, Jonathan C.; Shah, Malay B.; El Haddad, Hanine E.; El-Husseini, Amr; Dela Cruz, Anna C.; Grigorian, Alla; Mei, Xiaonan; Gedaly, Roberto
Abstract: Background: We aimed to study outcomes in HIV + patients with HCC in the US following Liver Transplantation (LT) using the UNOS dataset. Methods: The database was queried from 2003 to 2016 for patients undergoing LT with HCC, HIV+, and HCC/HIV+. Results: Out of 17, 397 LT performed for HCC during the study period, 113 were transplanted for HCC with HIV infection (91 isolated livers). Patients transplanted for HCC/HIV+ were younger (55.54 ± 5.89 vs 58.80 ± 7.37, p < 0.001), had lower total bilirubin (1.20 vs 1.60, p = 0.042) significantly lower BMI (25.35 ± 4.43 vs 28.39 ± 5.17, p < 0.001) and were more likely to be co-infected with HBV (25.3% vs 8.2% p < 0.001) than those transplanted for HCC alone. HCC/HIV + patients were found to have a 3.8 fold increased risk of peri-operative mortality at 90 days after matching. HCC/HIV + recipients had 54% decreased long-term survival within the HCC cohort. Our initial analysis of overall graft and patient survival found significant differences between HCC/HIV and HCC/HIV + recipients. However, these variances were lost after case-matching. Recurrence and disease free survival were similar in HCC alone vs HCC/HIV + recipients. Conclusions: Our analysis suggests that excellent outcomes can be achieved in selected patients with HCC/HIV+.